Reversible glacial-periglacial transition in response to climate changes and paraglacial dynamics: a case study from Héðinsdalsjökull (northern Iceland) - Palacios, David (2021)
The objective of this work is to chronologically establish the origin of the different glacial and rock glacier complex landforms deposited by Héðinsdalsjökull glacier (65°39′ N, 18°55′ W), in the Héðinsdalur valley (Skagafjörður fjord, Tröllaskagi peninsula, central northern Iceland). Multiple methods were applied: geomorphological analysis and mapping, glacier reconstruction and equilibrium-line altitude calculation, Cosmic-Ray Exposure dating (in situ cosmogenic 36Cl), and lichenometric dating. The results reveal that a debris-free glacier receded around 6.6 ± 0.6 ka, during the Holocene Thermal Maximum. The retreat of the glacier exposed its headwall and accelerated paraglacial dynamics. As a result, the glacier terminus evolved into a debris-covered glacier and a rock glacier at a slightly higher elevation. The front of this rock glacier stabilized shortly after it formed, although nuclide inheritance is possible, but its sector close the valley head stabilized between 1.5 and 0.6 ka. The lowest part of the debris-covered glacier (between 600 and 820 m altitude) collapsed at ca. 2.4 ka. Since then, periods of glacial advance and retreat have alternated, particularly during the Little Ice Age. The maximum advance during this phase occurred in the 15th to 17th centuries with subsequent re-advances, namely at the beginning of the 19th and 20th centuries. After a significant retreat during the first decades of the 20th century, the glacier advanced in the 1960s to 1990s, and then retreated again, in accordance with the local climatic evolution. The internal ice of both the debris-covered and the rock glacier have survived until the present day, although enhanced subsidence provides evidence of their gradual degradation. A new rock glacier developed from an ice-cored moraine from around 1940–1950 CE. Thus, the Holocene coupling between paraglacial and climatic shifts has resulted in a complex evolution of Héðinsdalsjökull, which is conflicting with previously proposed models: a glacier, which had first evolved into a debris-covered and rock glacier, could later be transformed into a debris-free glacier, with a higher sensitivity to climatic variability.